Formation method of semi-solid-state lithium battery and semi-solid-state lithium battery

By dividing the semi-solid lithium battery into small current charging, oscillation cycle and pressure polymerization stages in the decomposition method of semi-solid lithium battery, combined with the small current oscillation cycle and the pressure application during negative electrode expansion, the problem of poor curing uniformity of gel electrolyte in semi-solid lithium battery is solved, and the high-temperature storage performance and production consistency of the battery are improved.

CN119601807APending Publication Date: 2025-03-11JIANGSU PYLON BATTERY CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411788357.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

In practical applications, semi-solid lithium batteries have problems such as poor in-situ curing uniformity of gel electrolytes, poor interfacial stability and battery consistency, making it difficult to standardize large-scale production.

Method used

A synthesis method is adopted, including a small current charging stage, an oscillation cycle stage and a pressurized polymerization stage. By performing a small current oscillation cycle in the SOC interval with the fastest expansion rate of the negative electrode, and applying pressure at the SOC with the largest expansion degree of the negative electrode, the in-situ polymerization of the electrolyte and the bonding with the pores of the electrode are achieved.

Benefits of technology

The in-situ curing uniformity of gel electrolyte and the high-temperature storage performance of the battery are significantly improved, and the production consistency of the battery and the dispersion of the capacity are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601807A_ABST
    Figure CN119601807A_ABST
Patent Text Reader

Abstract

The invention discloses a formation method of a semi-solid-state lithium battery and the semi-solid-state lithium battery, and relates to the technical field of lithium ion batteries. The formation process is divided into a low-current charging stage, an oscillation circulation stage and a pressurization polymerization stage, low-current oscillation circulation is performed in an SOC interval with the fastest expansion rate of negative electrode graphite, so that sufficient and uniform huff and puff and film formation of an electrolyte are realized in a battery cell, and the film formation integrity and the electrolyte infiltration degree of the battery cell are improved; according to the present invention, the pressure is set at the SOC position with the maximum expansion degree of the negative electrode graphite, and the pressurization is combined with the highest expansion time of the negative electrode graphite, such that the adhesion of the electrolyte to the interior and the surface layer of the pole piece pore during the in-situ polymerization process is well achieved so as to significantly improve the in-situ curing effect, such that the dispersion degree of the battery capacity is centralized. According to the semi-solid gel electrolyte formed by the formation method provided by the invention, the transmission path of Mn < 2 + > in the electrolyte is well hindered, and the high-temperature storage performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a formation method of a semi-solid lithium battery and a semi-solid lithium battery. Background Art

[0002] Liquid lithium batteries are one of the most widely used rechargeable battery technologies. They have been widely used in portable electronic devices, electric vehicles and energy storage systems due to their excellent performance and mature technology. Their liquid electrolytes have the characteristics of high ionic conductivity, good wettability and a wide operating temperature range. They can effectively support the rapid transmission of lithium ions between the positive and negative electrodes and achieve efficient charging and discharging processes. However, traditional organic liquid electrolytes inevitably produce side reactions during the charging and discharging process, which affects the battery life. At the same time, the flammability of their organic solvents has also aroused public concerns about the safety of liquid lithium batteries. This has prompted researchers to begin developing new electrolytes, such as semi-solid electrolytes and all-solid electrolytes, to further improve the safety and electrical performance of batteries.

[0003] Semi-solid electrolytes can better combine the advantages of liquid electrolytes and solid electrolytes while overcoming the disadvantages of both. They are safer than liquid electrolytes, have longer cycle life, and are more resistant to extrusion and vibration. At the same time, their preparation process is simpler and less expensive than all-solid-state batteries, and they are expected to be quickly mass-produced and applied.

[0004] However, there are still many problems in the practical application of semi-solid electrolytes, such as the limited material selection, the need to accurately control the solvent ratio, the amount of cross-linker and initiator, and the curing conditions; at the same time, the interface stability and battery consistency are poor. Although semi-solid electrolytes can improve the electrode-electrolyte interface contact, in some cases, the interface stability is greatly affected by external temperature, humidity, pressure, etc. At present, a large number of patents have been explored for different monomer types and their application methods, but the problem of uniformity of curing of the formed gel electrolyte has not been fundamentally solved, the battery consistency is poor, and it is difficult to achieve standardized large-scale production on the production line due to the limitations of the battery shell and capacity.

[0005] Therefore, there is an urgent need to improve the in-situ curing uniformity of gel electrolytes and improve the consistency of semi-solid-state batteries in mass production.

[0006] In view of this, the present invention is proposed. Summary of the invention

[0007] The purpose of the present invention is to provide a formation method of a semi-solid lithium battery and a semi-solid lithium battery, aiming to significantly improve the in-situ curing uniformity of the gel electrolyte and improve the high-temperature storage performance of the battery.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a formation method of a semi-solid lithium battery, comprising:

[0010] Injecting electrolyte containing polymerization monomer and initiator into the dry battery cell, and then forming after aging, and controlling the forming temperature to be 45°C-50°C;

[0011] The formation process is as follows:

[0012] Low current charging stage: first charge with a constant current of less than or equal to 0.05C, and the cut-off voltage is 3.0V-3.5V;

[0013] Oscillation cycle stage: discharge at a constant current of 0.35C-0.45C to 2.0V-2.8V, then charge at a constant current of 0.35C-0.45C to 3.0V-3.5V, and oscillate and cycle at this rate;

[0014] Pressurized polymerization stage: Under pressure, charge at a constant current of 0.55C-0.65C to the target voltage.

[0015] In an optional embodiment, in the low current charging stage, the battery is first charged at a constant current of 0.01C-0.03C for 110min-130min, and then charged at a constant current of 0.03C-0.05C for 200min-220min;

[0016] And / or, the cut-off voltage in the low current charging stage is 3.1V-3.3V.

[0017] In an optional embodiment, during the oscillation cycle stage, the battery is discharged at a constant current of 0.38C-0.42C to 2.5V-2.8V, and then charged at a constant current of 0.38C-0.42C to 3.1V-3.3V, and oscillated and cycled at this rate;

[0018] And / or, during the oscillation cycle stage, controlling the oscillation cycle for 5 to 12 weeks.

[0019] In an optional embodiment, during the pressurized polymerization stage, the applied pressure is controlled to be 0.02MPa-0.08MPa, preferably 0.04MPa-0.06MPa;

[0020] And / or, during the pressurized polymerization stage, the battery is charged at a constant current of 0.55C-0.65C to 4.0V-4.2V, and then left at a voltage of 4.0V-4.2V for 2h-6h to complete the formation.

[0021] In an optional embodiment, the temperature for aging is 20°C-30°C, and the time for aging is 40h-55h.

[0022] In an optional embodiment, the electrolyte includes, by mass fraction, 90%-98% of a basic lithium salt electrolyte, 0.5%-10% of a polymerizable monomer, and 0.05%-0.1% of a thermal initiator.

[0023] In an optional embodiment, the polymerizable monomer is selected from at least one of polycarbonates, polyacrylates, polyamides and polyethers; more preferably, the polymerizable monomer is polyacrylate; further preferably, the polymerizable monomer is selected from at least one of methyl methacrylate, ethyl acrylate, butyl acrylate and hydroxyethyl acrylate;

[0024] Preferably, the thermal initiator is selected from at least one of a peroxide initiator and an azo initiator.

[0025] In an optional embodiment, the base lithium salt electrolyte contains 1%-2% of an unsaturated olefin additive, and the unsaturated olefin additive is selected from at least one of vinylene carbonate (VC), 1,3-propane sultone (PS) and methyl methane disulfonate (MMDS).

[0026] In an optional embodiment, the dry battery cell includes a positive electrode sheet, a negative electrode sheet and a separator, and the positive electrode active material in the positive electrode sheet is selected from at least one of a lithium manganese oxide positive electrode material, a lithium iron manganese phosphate positive electrode material, a lithium iron phosphate positive electrode material, a ternary nickel cobalt manganese positive electrode material and a nickel manganese oxide lithium positive electrode material;

[0027] The negative electrode active material in the negative electrode sheet is graphite.

[0028] In a second aspect, the present invention provides a semi-solid lithium battery prepared by the formation method of any one of the aforementioned embodiments.

[0029] The present invention has the following beneficial effects: the present invention improves the formation method of the semi-solid lithium battery, and divides the formation process into a small current charging stage, an oscillating cycle stage, and a pressurized polymerization stage. A small current oscillating cycle is performed in the SOC range where the negative electrode graphite expands the fastest, so that the electrolyte can be fully and evenly vented and film-formed inside the battery cell, thereby improving its film formation integrity and electrolyte infiltration degree; at the SOC where the negative electrode graphite expands the most, pressure is set, and pressurization is combined with the highest expansion time of the negative electrode graphite, thereby better achieving the adhesion of the electrolyte to the inside and surface of the electrode pores during the in-situ polymerization process, so that its in-situ curing effect is significantly improved, so that the battery capacity is more dispersed. The semi-solid gel electrolyte formed by the formation method provided by the present invention better hinders the Mn 2+ The transport path in the electrolyte improves the high-temperature storage performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0031] Figure 1 The semi-solid electrolyte provided in Example 1 of the present invention and the liquid electrolyte provided in the comparative example are compared for the first effect. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0033] The formation method provided in the embodiment of the present invention adopts a formation-while-polymerization process without changing the formation temperature. A small current oscillation cycle is performed in the SOC range where the negative electrode graphite expands the fastest, so that the electrolyte can be fully and evenly discharged inside the battery cell. At the SOC where the negative electrode expands the most, the battery is placed under pressurized constant pressure to enhance the fit between the electrolyte and the electrode, significantly improve its in-situ curing effect, and greatly improve the consistency of semi-solid battery production. At the same time, the scheme is also highly compatible with different monomers and initiators.

[0034] The embodiment of the present invention provides a formation method of a semi-solid lithium battery, the steps are as follows:

[0035] S1. Provide dry cells and electrolyte

[0036] The dry battery cell includes a positive electrode sheet, a negative electrode sheet and a separator, and can be prepared by a conventional lamination or winding process, or can be a commercially available dry battery cell.

[0037] In some embodiments, the positive electrode active material in the positive electrode sheet is selected from at least one of lithium manganese oxide positive electrode material, lithium iron manganese phosphate positive electrode material, lithium iron phosphate positive electrode material, ternary nickel cobalt manganese positive electrode material and nickel manganese oxide lithium positive electrode material. The type of positive electrode material can be any one or more of the above, and can also contain a small amount of doping elements, and the specific type is not limited. The type of positive electrode current collector is not limited, such as aluminum foil.

[0038] In some embodiments, the negative electrode active material in the negative electrode plate is graphite, such as artificial graphite. The type of the negative electrode current collector is not limited, such as copper foil.

[0039] According to the mass fraction, the electrolyte includes 90%-98% of the basic lithium salt electrolyte, 0.5%-10% of the polymerized monomer, and 0.05%-0.1% of the thermal initiator. The polymerized monomer and the thermal initiator can be added to the conventional basic lithium salt electrolyte, and the types of the polymerized monomer and the thermal initiator are not limited. Specifically, the mass fraction of the basic lithium salt electrolyte can be 90%, 93%, 95%, 98%, etc.; the mass fraction of the polymerized monomer can be 0.5%, 1.0%, 3.0%, 5.0%, 8.0%, 10.0%, etc.; the mass fraction of the thermal initiator can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.10%, etc.

[0040] In some embodiments, the base lithium salt electrolyte contains 1%-2% of unsaturated olefin additives, such as 1.0%, 1.5%, 2.0%, etc. The unsaturated olefin additive is selected from at least one of vinylene carbonate (VC), 1,3-propane sultone (PS) and methyl disulfonate (MMDS), and the type of unsaturated olefin additive can be any one or more of the above. The types of solvents and lithium salts of the base lithium salt electrolyte are not limited, and can be common lithium salts (such as LiPF6, the concentration can be 0.9-1.2 mol / L) and solvents (such as vinyl carbonate and methyl ethyl carbonate) of lithium battery electrolytes.

[0041] In some embodiments, the polymerizable monomer is selected from at least one of polycarbonates, polyacrylates, polyamides and polyethers. The polymerizable monomer may be any one or more of the above, and all are suitable for the chemical formation method provided in the embodiments of the present invention.

[0042] In a preferred embodiment, the polymerizable monomer is a polyacrylate. Compared with other monomers, the polyacrylate polymerizable monomer is more suitable for the chemical formation process provided by the embodiment of the present invention. After chemical formation, the in-situ curing effect is better, the pole piece is more closely fitted, and the dispersion of the battery capacity is more concentrated. More preferably, the polymerizable monomer is selected from at least one of methyl methacrylate, ethyl acrylate, butyl acrylate and hydroxyethyl acrylate. The polymerizable monomer can be any one or more of the above. After chemical formation by the chemical formation process provided by the embodiment of the present invention, the in-situ curing effect is very ideal, and the battery capacity can be better utilized.

[0043] In some embodiments, the thermal initiator is selected from at least one of a peroxide initiator and an azo initiator, and the thermal initiator can be any one or more of the above, such as dicumyl peroxide, benzoyl peroxide, azobisisobutyronitrile, azobisisoheptanenitrile, etc. The thermal initiation conditions are high temperature thermal polymerization, the polymerization temperature is 45°C-60°C, and the polymerization time is 4h-15h.

[0044] S2, injection, aging

[0045] The electrolyte containing polymerization monomers and initiators is injected into the dry battery cell, and the battery cell is subjected to chemical formation after being placed aside for aging, so that the electrolyte is fully infiltrated by the placing aside for aging.

[0046] In some embodiments, the aging temperature is 20°C-30°C, and the aging time is 40h-55h. By adjusting the aging temperature and time, the wetting effect of the electrolyte is further increased, so as to subsequently improve the uniformity of in-situ curing.

[0047] Specifically, the shelf aging is to leave the battery cells at a certain temperature, and the temperature of the shelf aging can be controlled to be 20°C, 23°C, 25°C, 28°C, 30°C, etc., and the shelf aging time can be 40h, 43h, 50h, 53h, 55h, etc.

[0048] S3, formation

[0049] After aging, transfer to a temperature and pressure controllable forming machine for forming, and control the forming temperature to be 45°C-50°C (such as 45°C, 48°C, 50°C, etc.). The forming process is as follows:

[0050] (a) Low current charging stage

[0051] First, charge at a constant current of 0.05C or less, with a cut-off voltage of 3.0V-3.5V, to ensure that the electrolyte is fully film-formed at this stage. Specifically, the charging current at this stage can be 0.01C, 0.02C, 0.03C, 0.04C, 0.05C, etc., and the cut-off voltage can be 3.0V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, etc.

[0052] In a preferred embodiment, in the low current charging stage, the battery is first charged at a constant current of 0.01C-0.03C for 110min-130min, and then charged at a constant current of 0.03C-0.05C for 200min-220min; the cut-off voltage in the low current charging stage is 3.1V-3.3V. By precisely controlling the charging current, time and cut-off voltage in the low current charging stage, the electrolyte is fully filmed in this stage.

[0053] Specifically, the time for constant current charging at a current of 0.01C-0.03C can be 110min, 115min, 120min, 125min, 130min, etc.; the time for constant current charging at a current of 0.03C-0.05C can be 200min, 205min, 210min, 215min, 220min, etc.

[0054] (b) Oscillation cycle stage:

[0055] Discharge at a constant current of 0.35C-0.45C to 2.0V-2.8V, and then charge at a constant current of 0.35C-0.45C to 3.0V-3.5V (i.e. the cut-off voltage in the low-current charging stage), and oscillate and cycle at this rate. Perform low-current oscillation cycles in the SOC range where the negative electrode graphite expands fastest, so that the electrolyte can be fully and evenly discharged and film-formed inside the battery cell, improving its film formation integrity and electrolyte infiltration.

[0056] Specifically, the current of constant current discharge can be 0.35C, 0.38C, 0.40C, 0.42C, 0.45C, etc., and the voltage after constant current discharge can be 2.0V, 2.1V, 2.2V, 2.3V, 2.4V, 2.5V, 2.6V, 2.7V, 2.8V, etc.; the current of constant current charging can be 0.35C, 0.38C, 0.40C, 0.42C, 0.45C, etc., and the voltage after constant current charging can be 3.0V, 3.1V, 3.2V, 3.3V, 3.4V, 3.5V, etc.

[0057] In a preferred embodiment, during the oscillation cycle stage, the battery is discharged at a constant current of 0.38C-0.42C to 2.5V-2.8V, and then charged at a constant current of 0.38C-0.42C to 3.1V-3.3V, and oscillated at this rate. By adjusting the current and voltage of constant current discharge and constant current charging, the electrolyte can be more fully and evenly discharged and film-formed inside the battery cell, further improving its film formation integrity and electrolyte infiltration degree.

[0058] Furthermore, in the oscillation cycle stage, the oscillation cycle is controlled to be 5 to 12 weeks, such as 5 weeks, 8 weeks, 9 weeks, 10 weeks, 11 weeks, 12 weeks, etc.

[0059] (c) Pressurized polymerization stage

[0060] Under the condition of applying pressure, the battery is charged to the target voltage at a constant current of 0.55C-0.65C. The pressure is set at the SOC where the negative electrode graphite expands the most. The pressure is combined with the highest expansion time of the negative electrode graphite to better achieve the adhesion of the electrolyte to the inside and surface of the electrode pores during the in-situ polymerization process, which significantly improves the in-situ curing effect, so the battery capacity is more dispersed.

[0061] Specifically, the charging current in the pressurized polymerization stage can be 0.55C, 0.58C, 0.60C, 0.63C, 0.65C, etc.

[0062] Furthermore, in the pressurized polymerization stage, the applied pressure is controlled to be 0.02MPa-0.08MPa, preferably 0.04MPa-0.06MPa, and the pressure in the pressurized polymerization stage is adjusted to promote the in-situ polymerization of the electrolyte and enhance the bonding effect with the inside of the pores and the surface of the electrode. Specifically, the applied pressure can be 0.02MPa, 0.03MPa, 0.04MPa, 0.05MPa, 0.06MPa, 0.07MPa, 0.08MPa, etc.

[0063] In some embodiments, during the pressurized polymerization stage, the battery is charged to 4.0V-4.2V at a constant current of 0.55C-0.65C, and then left at a voltage of 4.0V-4.2V for 2h-6h to complete the formation. Specifically, the target voltage may be 4.0V, 4.1V, 4.2V, etc., and the left-standing time at the voltage may be 2h, 3h, 4h, 5h, 6h, etc.

[0064] The embodiment of the present invention also provides a semi-solid lithium battery, which is prepared by the chemical formation method provided by the embodiment of the present invention. The gel electrolyte formed by in-situ curing can be attached to the inside and surface of the pores of the electrode, so that the battery capacity is more dispersed, which is conducive to the improvement of capacity; the semi-solid gel electrolyte formed has a good barrier to the Mn 2+ The transport path in the electrolyte improves the high-temperature storage performance of the battery.

[0065] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0066] Example 1

[0067] This embodiment provides a formation method for a semi-solid lithium battery, the steps are as follows:

[0068] (1) Provide dry cells and electrolyte

[0069] The dry cell is a self-made battery of our company. The positive electrode sheet includes a positive current collector and a positive electrode membrane arranged on the positive current collector. The positive electrode membrane is composed of lithium manganese oxide and lithium manganese iron phosphate (LMO:LMFP=7:3), SP, CNT, and PVDF in a mass ratio of 96:1.5:0.5:2.0, and the double-sided surface density is 480g / m 2 The negative electrode sheet includes a negative electrode current collector and a negative electrode membrane arranged on the negative electrode current collector. The negative electrode membrane is composed of graphite, CMC, SP and SBR in a mass ratio of 96:1.2:1.0:1.8, and the double-sided surface density is 189g / m 2 ; Finally, a 20μm PP separator was used for lamination to obtain the dry battery cell.

[0070] Battery case: soft pack; Battery capacity: 25Ah.

[0071] The electrolyte composition is: 96.9% basic lithium salt electrolyte, 3% polymerization monomer methyl methacrylate, and 0.1% initiator (AIBN). Among them, the lithium salt in the basic lithium salt electrolyte is LiPF6, the concentration can be 1 mol / L, the solvent is ethylene carbonate and ethyl methyl carbonate (volume ratio is 1:1), the additives are 0.5% VC and 1.0% PS, and the additive addition amount is 1.5%.

[0072] The polymerizable monomer is polyacrylate, specifically polymethyl methacrylate (PMMA), with a weight average molecular weight of 100,000 to 150,000 g / mol. The specific structure is as follows:

[0073]

[0074] (2) Liquid injection and aging

[0075] After the dry cell is filled with liquid, it is placed at 25℃ for 48 hours for aging, and then transferred to a temperature and pressure controllable forming machine for forming at 45℃.

[0076] (3)Chemification

[0077] First, charge at a low current of 0.02C for 120 minutes, then charge at a constant current of 0.04C for 210 minutes, with a cut-off voltage of 3.2V, to ensure that the electrolyte is fully filmed at this stage. Discharge at a constant current of 0.4C to 2.7V, then charge at a constant current of 0.4C to 3.2V, and oscillate at this rate for 10 cycles, without formation pressure constraints. After the oscillation cycle is completed, continue to charge at a constant current of 0.6C to 4.1V, and adjust the pressure of the formation machine to 0.05MPa, and leave it at this voltage for 4h to complete the formation.

[0078] Example 2

[0079] The only difference from Example 1 is that the formation step of step (3) is as follows:

[0080] First, charge at a low current of 0.02C for 120 minutes, then charge at a constant current of 0.04C for 210 minutes, with a cut-off voltage of 3.2V, to ensure that the electrolyte is fully filmed at this stage. Discharge at a constant current of 0.4C to 2.7V, then charge at a constant current of 0.4C to 3.2V, and oscillate at this rate for 10 cycles, without formation pressure constraints. After the oscillation cycle is completed, continue to charge at a constant current of 0.6C to 4.1V, and adjust the pressure of the formation machine to 0.05MPa, and leave it at this voltage for 6 hours to complete the formation.

[0081] Example 3

[0082] The only difference from Example 1 is that the formation step of step (3) is as follows:

[0083] First, charge at a low current of 0.02C for 120 minutes, then charge at a constant current of 0.04C for 210 minutes, with a cut-off voltage of 3.2V, to ensure that the electrolyte is fully filmed at this stage. Discharge at a constant current of 0.4C to 2.7V, then charge at a constant current of 0.4C to 3.2V, and oscillate at this rate for 10 cycles, without formation pressure constraints. After the oscillation cycle is completed, continue to charge at a constant current of 0.6C to 4.1V, and adjust the pressure of the formation machine to 0.025MPa, and leave it at this voltage for 6 hours to complete the formation.

[0084] Example 4

[0085] The only difference from Example 1 is that the type of polymerization monomer in step (1) is different. This example uses polycarbonate, specifically bisphenol A polycarbonate, with a weight average molecular weight of 20,000 to 40,000 g / mol. The specific structure is as follows:

[0086]

[0087] Example 5

[0088] The only difference from Example 1 is that the type of polymerization monomer in step (1) is different. This example uses polyethers, specifically isopentyl polyoxyethylene ether (TPEG), with a weight average molecular weight of 600 to 1,000 g / mol. The specific structure is as follows:

[0089]

[0090] Example 6

[0091] The only difference from Example 1 is that the type of polymerization monomer in step (1) is different. This example uses polyamide, specifically polyhexamethylene adipamide (PA66), with a weight average molecular weight of 15,000 to 25,000 g / mol. The specific structure is as follows:

[0092]

[0093] Example 7

[0094] The only difference from Example 1 is that during the formation process in step (3), the number of oscillation cycles is changed to 5 cycles.

[0095] Example 8

[0096] The only difference from Example 1 is that during the formation process in step (3), the formation temperature is changed to 50°C.

[0097] Example 9

[0098] The only difference from Example 1 is that during the formation process of step (3), the standby voltage during pressurized standby polymerization is changed to 4.2V.

[0099] Comparative Example 1

[0100] This comparative example provides a liquid electrolyte for comparison, and the only difference from Example 1 is that no polymerization monomer and initiator are added in step (1).

[0101] Comparative Example 2

[0102] The only difference from the embodiment is that the formation step of step (3) is as follows: it does not contain the step of 2.7-3.2V oscillation cycle.

[0103] Comparative Example 3

[0104] The only difference from the embodiment is that the formation step of step (3) is as follows: no pressure is applied during polymerization.

[0105] Comparative Example 4

[0106] The only difference from the embodiment is that the formation step of step (3) is as follows:

[0107] In the first stage, the current of the segmented small current formation was changed to 0.04C, the constant current charging time was 270min, and the cut-off voltage was 3.2V.

[0108] Test Example 1

[0109] The first performance of the lithium battery was obtained by testing Example 1 and Comparative Example 1. The results are as follows: Figure 1 shown.

[0110] The first efficiency is calculated by dividing the discharge capacity of the battery cell in the first week by the total capacity of the first charge.

[0111] It can be seen that the first effect concentration of the semi-solid electrolyte provided by the embodiment of the present invention is slightly better than that of the liquid electrolyte.

[0112] Test Example 2

[0113] The rate discharge performance and high temperature storage performance of the batteries prepared in the test examples and comparative examples are shown in Table 1.

[0114] Test method:

[0115] (1) 25℃ rate discharge: ① Charge at 0.5C constant current and constant voltage at 25℃, and discharge at 0.5C constant current for three cycles to constant capacity (voltage range 2.5-4.2V); ② Charge at 0.5C constant current and constant voltage to 4.2V, with a cut-off current of 0.05C; ③ Leave for 30 minutes, and then discharge at 2.0C constant current to 2.5V; ④ End.

[0116] (2) Fully charged storage at 55℃: ① Discharge at 0.5C constant current to 2.5V at 25℃; ② Leave for 30 minutes, then charge at 0.05C constant current and constant voltage to 4.2V; ③ Leave for 30 minutes, discharge at 0.5C constant current to 2.5V, and repeat steps ② to ③ three times to fix the capacity; ④ Leave for 30 minutes, then charge at 0.05C constant current and constant voltage to 4.2V to fully charge the battery; ⑤ Transfer the fully charged battery to a 55℃ incubator and leave for 7 days, then remove and repeat steps ① to ④ once.

[0117] Table 1 Rate discharge performance and high temperature storage performance of the batteries prepared in the examples and comparative examples

[0118]

[0119] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A formation method for a semi-solid lithium battery, characterized in that: include: Injecting electrolyte containing polymerization monomer and initiator into the dry battery cell, and then forming after aging, and controlling the forming temperature to be 45°C-50°C; The formation process is as follows: Low current charging stage: first charge with a constant current of less than or equal to 0.05C, and the cut-off voltage is 3.0V-3.5V; Oscillation cycle stage: discharge at a constant current of 0.35C-0.45C to 2.0V-2.8V, then charge at a constant current of 0.35C-0.45C to 3.0V-3.5V, and oscillate and cycle at this rate; Pressurized polymerization stage: Under pressure, charge at a constant current of 0.55C-0.65C to the target voltage.

2. The chemical formation method according to claim 1, characterized in that: In the low current charging stage, the battery is first charged at a constant current of 0.01C-0.03C for 110min-130min, and then charged at a constant current of 0.03C-0.05C for 200min-220min; And / or, the cut-off voltage of the small current charging stage is 3.1V-3.3V.

3. The chemical formation method according to claim 1, characterized in that: In the oscillation cycle stage, the battery is discharged to 2.5V-2.8V at a constant current of 0.38C-0.42C, and then charged to 3.1V-3.3V at a constant current of 0.38C-0.42C, and oscillated and cycled at this rate; And / or, during the oscillation cycle stage, the oscillation cycle is controlled to be 5 to 12 cycles.

4. The chemical formation method according to claim 1, characterized in that: In the pressurized polymerization stage, the applied pressure is controlled to be 0.02MPa-0.08MPa, preferably 0.04MPa-0.06MPa; And / or, in the pressurized polymerization stage, the battery is charged to 4.0V-4.2V at a constant current of 0.55C-0.65C, and then left at a voltage of 4.0V-4.2V for 2h-6h to complete the formation.

5. The chemical formation method according to claim 1, characterized in that: The temperature for aging is 20°C-30°C, and the time for aging is 40h-55h.

6. The chemical formation method according to claim 1, characterized in that: Calculated by mass fraction, the electrolyte includes 90%-98% of basic lithium salt electrolyte, 0.5%-10% of polymerized monomer, and 0.05%-0.1% of thermal initiator.

7. The chemical formation method according to claim 6, characterized in that: The polymerizable monomer is selected from at least one of polycarbonates, polyacrylates, polyamides and polyethers; more preferably, the polymerizable monomer is polyacrylate; further preferably, the polymerizable monomer is selected from at least one of methyl methacrylate, ethyl acrylate, butyl acrylate and hydroxyethyl acrylate; Preferably, the thermal initiator is selected from at least one of a peroxide initiator and an azo initiator.

8. The chemical formation method according to claim 6, characterized in that: The basic lithium salt electrolyte contains 1%-2% of an unsaturated olefin additive, and the unsaturated olefin additive is selected from at least one of vinylene carbonate, 1,3-propane sultone and methyl methane disulfonate.

9. The chemical formation method according to claim 1, characterized in that: The dry battery cell comprises a positive electrode sheet, a negative electrode sheet and a separator, wherein the positive electrode active material in the positive electrode sheet is selected from at least one of a lithium manganese oxide positive electrode material, a lithium iron manganese phosphate positive electrode material, a lithium iron phosphate positive electrode material, a ternary nickel cobalt manganese positive electrode material and a nickel manganese oxide lithium positive electrode material; The negative electrode active material in the negative electrode plate is graphite.

10. A semi-solid lithium battery, characterized in that: It is prepared by the chemical formation method described in any one of claims 1 to 9.

Citation Information

Cited By

  • A semi-solid lithium battery and a formation method thereof

    CN122739551A